Effect of essential oil obtained from Croton cajucara Benth. on gastric ulcer healing and protective factors of the gastric mucosa - Hiruma-Lima, C. A. [UNESP]; Gracioso, J. S.; Bighetti, E. J. B.; Grassi-Kassisse, D. M.; Nunes, D. S.; Brito, A. R. M. Souza (Urban & Fischer Verlag, 2002)
The bark of Croton cajucara Benth. (Euphorbiaceae) is used widely in Amazonian folk medicine for the treatment of a wide range of gastrointestinal symptoms. Infusions of C. cajucara bark contain dehydrocrotonin (DHC), the furan diterpene, and an essential oil, a rich mixture of sesquiterpenes. Although the antiulcerogenic activity of the essential oil has been studied in different gastric ulcer models in mice and rats, its mechanism remains unclear. In this work, we examined the ability of this essential oil to increase PGE(2) release from mucus cells, as well as its effects on the amount of gastric mucus and on the healing of acetic acid-induced gastric ulcers. The essential oil (100 mg/kg body wt., p.o). significantly increased PGE(2) production by glandular cells (by 102% as compared to control) and the amount of Alcian blue binding to the gastric mucus. In chronic gastric ulcers, a single daily oral dose of essential oil (100 mg/kg body wt.) for 14 consecutive days accelerated ulcer healing to an extent similar to that seen with an equal dose of cimetidine. Thus, the protective and healing actions of the essential oil from C. cajucara bark on gastric lesions resulted mainly from an increase in PGE(2) release and gastric mucus formation which would protect the gastric mucosa.
Keywords: Croton cajucara; gastric cytoprotection; healing effect; essential oil